2010
DOI: 10.1038/mp.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of ZNF804A and genome-wide significant evidence for its involvement in schizophrenia and bipolar disorder

Abstract: A recent genome wide association study reported evidence for association between rs1344706 within ZNF804A (encoding zinc finger protein 804A) and schizophrenia (P=1.61 ×10−7), and stronger evidence when the phenotype was broadened to include bipolar disorder (P=9.96 ×10−9). Here we provide additional evidence for association through meta-analysis of a larger dataset (schizophrenia/schizoaffective disorder N = 18945, schizophrenia plus bipolar disorder N =21274, controls N =38675). We also sought to better loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
207
3
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(222 citation statements)
references
References 31 publications
9
207
3
3
Order By: Relevance
“…Consistent with previous studies (Riley et al, 2010;Williams et al, 2011;Steinberg et al, 2011;Zhang et al, 2011;Xiao et al, 2011, see Li et al, 2011, for an exception), the current study found evidence for the association between rs1344706 and schizophrenia. In addition, we replicated results of Walters et al (2010) that the association between rs1344706 and schizophrenia became stronger when the samples were limited to those with relatively high IQ.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies (Riley et al, 2010;Williams et al, 2011;Steinberg et al, 2011;Zhang et al, 2011;Xiao et al, 2011, see Li et al, 2011, for an exception), the current study found evidence for the association between rs1344706 and schizophrenia. In addition, we replicated results of Walters et al (2010) that the association between rs1344706 and schizophrenia became stronger when the samples were limited to those with relatively high IQ.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, an intronic SNP in this gene, rs1344706, has been found to be one of the most compelling candidate SNPs for schizophrenia. As shown by a recent whole genome study (O'Donovan et al, 2008) and several follow-up replications (Riley et al, 2010;Williams et al, 2011;Steinberg et al, 2011), there is a strong association between this SNP and schizophrenia with the A allele being the risk allele. This association has also been replicated among Han Chinese population in two studies Xiao et al, 2011) but not a third one .…”
Section: Introductionmentioning
confidence: 89%
“…For this, it is necessary to compare cDNA allele ratios in heterozygotes for the risk variant (where any cis ‐regulatory effects of the two alleles will differ) with those in homozygotes for the risk variant (where any cis ‐regulatory effects of the variant will be equal) [Bray et al, 2003a, 2005; Williams et al, 2011; Hill and Bray, 2012]. Small genotype groups precluded such an assessment of cis ‐regulatory effects of rs11191419, but genotype at ch10_104957618_I was associated with significant effects on the allelic expression of BORCS7 in fetal brain, adult DLPFC, adult hippocampus and adult caudate, AS3MT in the fetal brain and adult caudate, and NT5C2 in the fetal brain, adult DLPFC and adult hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that other white matter tracts, not examined in this study, might have been influenced by this risk variant. In addition, although there is evidence to support the rs1344706 SNP as the actual risk variant within the ZNF804A gene (Riley et al, 2010;Williams et al, 2010), it is possible that a nearby SNP in linkage disequilibrium with rs1344706 may be the causative risk variant. Regarding cognitive performance, although a significant genotype by cognitive task interaction was found, our follow-up analysis demonstrating the effect of genotype on attention control would not have survived Bonferroni's correction.…”
Section: Discussionmentioning
confidence: 99%